Evaluation of trace elements status of dairy cattle, feed, fodder and soil at medium elevation in hills to establish soil-plant-animal relationship - KUMAR, BHUVNESH; PACHAURI, S P; KUMAR, NARENDRA (The Indian Journal of Animal Sciences, 2014)
Trace elements status of animals, feed, fodder and soil with respect to copper (Cu), iron (Fe), manganese (Mn), zinc (Zn) and cobalt (Co), was evaluated during summer (S1)and winter (S2)at 1700 m altitude from mean sea level in Central Himalayas to find out whether soil, feed,fodder and animals contain adequate levels of these elements and to establish soil-plant-animal relationship. Animals on their blood analysis had these elements adequately, however, green fodder (berseem and white clover) fed to the animals during summer was deficient in both Cu (3.62 ± 0.32  µg/g) and Zn (14.14 ± 0.43 µg/g) whereas, green fodder (green maize and maize stober) fed during winter was deficient in Zn (31.62 ± 2.75 µg/g). Dry fodder (wheat straw) was also inadequate in both Cu during S1 (7.59 ± 0.60 µg/g) and S2 (7.32 ± 0.55 µg/g) and Zn content during S, (7.86 ± 0.35 Ilglg) and Sz (8.16 ± 0.38 µg/g). Whereas, concentrate mixture contained these elements adequately to meet the nutritional requirement of animals. Hill soil was deficient in Zn during summer (1.53 ± 0.29 µg/g) but adequate in Cu, Fe, Mn, and Co to meet the needs of plant growth. Animals, green fodder and concentrate mixture showed significant seasonal variations in all of these trace elements (P